Transforming gender and emotion : the Butterfly Lovers story in China and Korea - Cho, Sookja (University of Michigan Press, 2018)
Often called China's "Romeo and Juliet", the story of the Butterfly Lovers (the tale of Liang Shanbo and Zhu Yingtai, or the Liang-Zhu story) is one of the most famous folk stories in traditional China. With its origins dating back to the fourth century, it has spread and evolved across genres, country, religion, and culture. Transforming Gender and Emotion examines how this story has successfully traveled and multiplied over the centuries, and elucidates what this phenomenon tells us about the story, the local peoples and cultures it represents and the cultural-literary relationship between China and Korea in premodern times. In particular, the book aims to examine the transmission and survivability of its transgressive elements, challenging social, gender, and emotional norms